2016
DOI: 10.1111/hir.12152
|View full text |Cite
|
Sign up to set email alerts
|

HIV information needs of parents of young men who have sex with men

Abstract: Delivery of tailored HIV prevention information to parents may be effective in helping combat HIV among YMSM. Given that YMSM bear the greatest burden for HIV, this study highlights the need to include parents of YMSM in future interventions aimed at reducing YMSM's risk of HIV/AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This highlights the need for school nurses to be trained in providing culturally competent care to diverse patients, including SGM youth. Similar to Rose and Friedman (2016), cultural competency training should begin during undergraduate studies and continuing education should be offered regularly to ensure school nurses are prepared and knowledgeable about health issues that impact SGM youth. Second, findings suggest that it would be beneficial for nurses to work with colleagues to update schools' current sexual health curricula to be inclusive of SGM individuals.…”
Section: Implications For School Nursing and School Sexual Health Sermentioning
confidence: 99%
“…This highlights the need for school nurses to be trained in providing culturally competent care to diverse patients, including SGM youth. Similar to Rose and Friedman (2016), cultural competency training should begin during undergraduate studies and continuing education should be offered regularly to ensure school nurses are prepared and knowledgeable about health issues that impact SGM youth. Second, findings suggest that it would be beneficial for nurses to work with colleagues to update schools' current sexual health curricula to be inclusive of SGM individuals.…”
Section: Implications For School Nursing and School Sexual Health Sermentioning
confidence: 99%
“…The impact of information, or lack of access to information, were issues of concern in studies conducted by Nelissen et al . and Rose et al . In their standardised cross‐sectional survey of 621 cancer‐diagnosed and 1387 non‐diagnosed individuals, Nelissen et al.…”
Section: In This Issue…mentioning
confidence: 99%
“…The lack of information targeted at parents of those most likely to be infected with HIV was the focus of Rose et al. 's study . Ten in‐depth interviews were conducted with parents of young men who have sex with men to identify their information needs, analysis indicating that parents need to have access to HIV prevention information to reduce the risk of HIV infection in family members.…”
Section: In This Issue…mentioning
confidence: 99%
See 1 more Smart Citation
“…Although many of these parents described a process through which they eventually became closer to their children by seeking education about LGBTQ issues, the period immediately after coming out may be a time during which LGBTQ youth are particularly vulnerable to negative health outcomes. With regard to sexual health, studies have found that many parents avoid discussing sexuality with their gay or bisexual male teens because they are uncomfortable talking about same-sex sexuality (LaSala, 2015) or because they lack knowledge about these issues (Rose & Friedman, 2016). However, general perceptions of parent-child closeness (as reported by both the parent and teen) are associated with less sexual risk behavior (LaSala, 2007, 2015), indicating that supportive relationships may buffer against negative sexual health outcomes.…”
mentioning
confidence: 99%